2015
DOI: 10.3390/md13127062
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship Study of the Neuritogenic Potential of the Glycan of Starfish Ganglioside LLG-3 ‡

Abstract: LLG-3 is a ganglioside isolated from the starfish Linchia laevigata. To clarify the structure-activity relationship of the glycan of LLG-3 toward rat pheochromocytoma PC12 cells in the presence of nerve growth factor, a series of mono- to tetrasaccharide glycan derivatives were chemically synthesized and evaluated in vitro. The methyl group at C8 of the terminal sialic acid residue was crucial for neuritogenic activity, and the terminal trisaccharide moiety was the minimum active motif. Furthermore, the trisac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…996 A trisaccharide fragment of the starsh ganglioside LLG-3 (Linckia laevigata) 997 promotes neurite extension in human neuroblastoma cells via MAPK/ERK signalling but not via Akt signalling. 998 Polyhydroxylated sterols from the Vietnamese urchin Diadema savignyi induce apoptosis in HTCLs via inactivation of the MAPK/ERK1/2 pathway 999 while sterols from the starsh Protoreaster nodosus were found to inhibit the production of pro-inammatory cytokines including IL-12 p40, IL-6 and TNF-a in LPS-stimulated bone marrow-derived dendritic cells. 1000 Puried saponins from Chinese collections of Holothuria moebii exhibited in vitro cytotoxicity towards a panel of HTCLs and a total saponin fraction (mixture) inhibited CT-26 tumour growth in mice.…”
Section: Echinodermsmentioning
confidence: 99%
“…996 A trisaccharide fragment of the starsh ganglioside LLG-3 (Linckia laevigata) 997 promotes neurite extension in human neuroblastoma cells via MAPK/ERK signalling but not via Akt signalling. 998 Polyhydroxylated sterols from the Vietnamese urchin Diadema savignyi induce apoptosis in HTCLs via inactivation of the MAPK/ERK1/2 pathway 999 while sterols from the starsh Protoreaster nodosus were found to inhibit the production of pro-inammatory cytokines including IL-12 p40, IL-6 and TNF-a in LPS-stimulated bone marrow-derived dendritic cells. 1000 Puried saponins from Chinese collections of Holothuria moebii exhibited in vitro cytotoxicity towards a panel of HTCLs and a total saponin fraction (mixture) inhibited CT-26 tumour growth in mice.…”
Section: Echinodermsmentioning
confidence: 99%
“…Yamagishi and colleagues explored the structure-activity relationship of LLG-3 (205), a ganglioside isolated from the starfish Linchia laevigata, and discovered that the methyl group at C8 of the terminal sialic acid residue was of critical significance for neuritogenic activity. Furthermore, detailed signaling studies revealed the "activation of mitogen-activated protein kinase signaling pathway" [221]. Cassiano and colleagues, using chemical proteomics, noted that the terpenoid heteronemin (206), isolated from the marine sponge Hyrtios sp., targeted TDP-43, a major component of inclusions that characterize amyotrophic lateral sclerosis and front-temporal lobar degeneration, by lowering its affinity "towards nucleic acids", and thus becoming a "relevant chemical tool in the study of TDP-43 related processes" [222].…”
Section: Marine Compounds Affecting the Nervous Systemmentioning
confidence: 99%
“…The chemical synthesis of several complex echinodermatous gangliosides has been demonstrated. We reported the synthesis of HPG-2, LLG-3, GGA-7, PNG-2A, and GP3, and other groups have disclosed the synthesis of Hp-s1 and DSG-A . Furthermore, we performed a structure–activity relationship (SAR) study of the ganglioside LLG-3 to reveal that the nonreducing trisaccharide with the 8- O -methyl group at the terminal sialic acid was the minimal active motif …”
mentioning
confidence: 98%
“…To accomplish methylation at the C9 hydroxyl group, 13 was subjected to the following two-step reaction sequence. The removal of the 9- O -chloroacetyl group was conducted by using a combination of 1-selenocarbamoylpiperidine 14 and 2,6-lutidine, developed in our laboratory, ,, which prevents the migration of the acetyl group from O8 to O9. The methylation of the resulting C9 hydroxyl group with Meerwein’s reagent (Me 3 OBF 4 ) and 2,6-di- tert -butyl-4-methylpyridine under refluxing conditions required a long reaction time and, unfortunately, led to the formation of a tiny amount of an undesired 8- O -methylated byproduct that was inseparable from the desired 9- O -methylated product 15 (data not shown).…”
mentioning
confidence: 99%